Women and the Islamic republic how gendered citizenship conditions the Iranian state - Saeidi, Shirin 1980- (Cambridge Middle East studies, 2022)
Based on extensive interviews and oral histories as well as archival sources, Women and the Islamic Republic challenges the dominant masculine theorizations of state-making in post-revolutionary Iran. Shirin Saeidi demonstrates that despite the Islamic Republic's non-democratic structures, multiple forms of citizenship have developed in post-revolutionary Iran. This finding destabilizes the binary formulation of democratization and authoritarianism which has not only dominated investigations of Iran, but also regime categorizations in political science more broadly. As non-elite Iranian women negotiate or engage with the state's gendered citizenry regime, the Islamic Republic is forced to remake, oftentimes haphazardly, its citizenry agenda. The book demonstrates how women remake their rights, responsibilities, and statuses during everyday life to condition the state-making process in Iran, showing women's everyday resistance to the state-making process